Esophageal Squamous Dysplasia is Common in Asymptomatic Kenyans: A Prospective, Community‐Based, Cross‐Sectional Study. (April 2016) - Mwachiro, Michael M; Burgert, Stephen L; Lando, Justus; Chepkwony, Robert; Bett, Collins; Bosire, Claire; Abnet, Christian C; Githanga, Jessie; Waweru, Wairimu; Giffen, Carol A; Murphy, Gwen; White, Russell E; et al.
Abstract : Objectives: Esophageal squamous cell carcinoma (ESCC) is endemic in east Africa and is a leading cause of cancer death among Kenyans. The asymptomatic precursor lesion of ESCC is esophageal squamous dysplasia (ESD). We aimed to determine the prevalence of ESD in asymptomatic adult residents of southwestern Kenya. Methods: In this prospective, community‐based, cross‐sectional study, 305 asymptomatic adult residents completed questionnaires and underwent video endoscopy with Lugol's iodine chromoendoscopy and mucosal biopsy for detection of ESD. Results: Study procedures were well tolerated, and there were no adverse events. The overall prevalence of ESD was 14.4% (95% confidence interval (CI): 10–19%), including 11.5% with low‐grade dysplasia and 2.9% with high‐grade dysplasia. The prevalence of ESD was >20% among men aged >50 years and women aged >60 years. Residence location was significantly associated with ESD (Zone A adjusted odds ratio (OR) 2.37, 95% CI: 1.06–5.30 and Zone B adjusted OR 2.72, 95% CI: 1.12–6.57, compared with Zone C). Iodine chromoendoscopy with biopsy of unstained lesions was more sensitive than white‐light endoscopy or random mucosal biopsy for detection of ESD and had 67% sensitivity and 70% specificity. Conclusions: ESD is common among asymptomatic residents of southwestern Kenya and is especially prevalent in persons aged >50 years and those living in particular local regions. Lugol's iodine chromoendoscopy is necessary for detection of most ESD but has only moderate sensitivity and specificity in this setting. Screening for ESD is warranted in this high‐risk population, and endoscopic screening of Kenyans is feasible, safe, and acceptable, but more accurate and less invasive screening tests are needed.